Force Entrepreneurship in Contemporary Russia. Part 4: Thieves and Gangsters - Вадим Викторович Волков (Journal of Economic Sociology, 2010)
The author analyzes the problem of continuity and changes in the underworld in Russia after the state socialism system broke down. There is an attempt of sociological reconstruction of basic characteristics of the thieves’ society, of understanding its system of norms and their functions in this part 4.  The contradictions and conflicts that appear due to the differences in the thieves’ and gangsters’ subcultures are in the focus. The author claims that the representatives of the traditional underworld played a key role in the post-soviet crime formation, however they had to adapt to the changing circumstances themselves.